Does the Individualist Consume More? The Interplay of Ethics and Beliefs that Governs Consumerism Across Cultures - Lee, Monle; Pant, Anurag; Ali, Abbas J. 1953- (2010)
Individualism leading to more consumerism seems to be a bit of truism nowadays in the media. The USA is particularly indicted for being too individualistic and consumerist. Past research has mostly indicated a positive relationship between the two. However, past research has not suggested a negative association between individualism and consumerism. This paper offers support for such a negative relationship by showing that an individual’s ethical values can temper the consumerist nature of individualists. Data were collected in the USA and Taiwan. Structural equation models demonstrate that our hypothesized model fits our data well. A key result over the global sample is the stability of the linear path from individualism to work ethic to consumer ethic to consumerism. The two-nation comparison also supports differences in how Taiwanese and Americans differ in their belief that consumption benefits society.
Keywords: Work Ethic; Protestant Work Ethic; Individualism; individual values; Ethical Behavior; Consumerism; Consumer Ethic